Internalisasi Nilai-Nilai Demokrasi Melalui Projek Penguatan Profil Pelajar Pancasila (P5) di SMAN 1 Kota Batu - Suyato Suyato; Ascosenda Ika Rizki; Arif Prasetyo Wibowo; Rose Fitria Lutfiana (Jurnal Civic Hukum, 2026)
This study aims to analyze the internalization of democratic values through the implementation of the Pancasila Student Profile Strengthening Project (P5) under the theme “Voice of Democracy” in the student council election at SMAN 1 Kota Batu.  Studies on the Pancasila Student Profile Strengthening Project (P5) have largely focused on program implementation and general character formation, while the internalization of democratic values through school-based democratic practices remains underexplored. This research employed a qualitative approach with a case study design. Data were collected through interviews, observation, and document analysis.  The research instruments include interview guidelines, observation guidelines, and documentation study guidelines. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing, while data trustworthiness was ensured through source and technique triangulation. The findings show that the student council election within P5 functions as a school-based democratic laboratory, not merely as an electoral routine. The internalization of democratic values occurs through three main stages: nomination and campaign, candidate debate, and voting and vote counting. These stages foster students’ responsibility, tolerance, reciprocity awareness, open-mindedness, sportsmanship, honesty, and procedural discipline. The study concludes that P5 under the “Voice of Democracy” theme provides a substantive democratic learning experience and contributes to strengthening students’ democratic attitudes within the framework of the Pancasila Student Profile.